2019
DOI: 10.1515/cclm-2018-1369
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of involved/uninvolved free light chain ratio determined by Freelite and N Latex FLC assays for identification of high-risk smoldering myeloma patients

Abstract: Background Smoldering multiple myeloma (SMM) is an asymptomatic plasma cell disorder with a high risk of progression to symptomatic multiple myeloma (MM). The serum free light chain (sFLC) ratio is a powerful prognostic factor for SMM: an sFLC ratio ≥8 has been reported to be associated with a high risk of progression to MM, and an sFLC ratio ≥100 has been described as a criterion for ultra-high-risk SMM, and has been integrated into the definition criteria for MM since 2014. However, all recommendations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…After eliminating duplicates, publications not addressing biomarker-defined MM or SMM, and publications without graphs suitable for data digitization, we ended up with 11 studies (non-randomized observational cohort studies) that were included in the meta-analysis. In addition to the six studies published up until the end of 2014, 10 , 11 , 12 , 13 , 14 , 15 which formed the basis of the current treatment guidelines, we identified five recent studies 21 , 22 , 23 , 24 , 25 containing data and diagrams that were viable for the meta-analysis, of which one contained novel data both on patients with increased BMPCs and on high FLCratio, 25 four on high FLCratio only, 21 , 22 , 23 , 24 , 25 and none on focal lesions. The data by Rago et al., 26 on the impact of BMPCs, albeit containing a suitable graph, were not used for the 2014 consensus.…”
Section: Resultsmentioning
confidence: 99%
“…After eliminating duplicates, publications not addressing biomarker-defined MM or SMM, and publications without graphs suitable for data digitization, we ended up with 11 studies (non-randomized observational cohort studies) that were included in the meta-analysis. In addition to the six studies published up until the end of 2014, 10 , 11 , 12 , 13 , 14 , 15 which formed the basis of the current treatment guidelines, we identified five recent studies 21 , 22 , 23 , 24 , 25 containing data and diagrams that were viable for the meta-analysis, of which one contained novel data both on patients with increased BMPCs and on high FLCratio, 25 four on high FLCratio only, 21 , 22 , 23 , 24 , 25 and none on focal lesions. The data by Rago et al., 26 on the impact of BMPCs, albeit containing a suitable graph, were not used for the 2014 consensus.…”
Section: Resultsmentioning
confidence: 99%
“…So clinicians should consider using the same assay for follow-up. 34 Although both testing systems are now used in diagnostic laboratories, the reference values and clinical cut-offs are specific, 17,35 but clinical cut-offs for N-Latex are still needed for AL-CA prognostic testing.…”
Section: Measuring Direct Free Light Chains With N-latex Technique Ma...mentioning
confidence: 99%
“…But with a worsening of renal function, the Sebia Free Light Chain Assay detected an increase in both serum kappa and lambda FLC, and an increase in the kappa/lambda sFLC ratio (16). A number of studies have concluded that the various sFLC assays are safe but not commutable, as the numerical results can vary drastically for individual patients, while the qualitative results and the trends in monitoring are in agreement (8,(10)(11)(12)17). Furthermore, all recommendations were established with Freelite ® assay.…”
mentioning
confidence: 97%
“…Consequently, the other tests cannot be used for staging, especially in clinical trials, irrespective of the performance of these tests (11,18,19). Nevertheless, few studies to date have documented the performance of other sFLC assays in these conditions (10,17).…”
mentioning
confidence: 99%